Perhitungan Harga Pokok Produksi dalam Penetapan Harga Jual dengan Metode Variable Costing pada Piscok Aneka Rasa di Jl. Ronggo Waluyo - Irziansyah, Rizki Lutfi; Nur‘Aini, Najmah; Ramadhan, Muhammad Daffa; Abdillah, Ken Ibnu; Chika, Nayla (Value : Journal of Management and Business, 2024)
This research challenges the influence of variable costing methodology on the pricing of various flavors of "piscok" at Jl Ronggo Waluyo. The study aims to: (1) delineate the production costs of "piscok" at Jl. Ronggo Waluyo, and (2) ascertain whether the manufacturing costs are determined using variable costing. Employing a quantitative approach and non-probability sampling, the study utilizes preliminary data obtained confidentially from Small and Medium Enterprises (SMEs), garnered through interviews with SME personnel and cost data acquired during the 2023 production cycle. Upon analyzing production costs and unit pricing for "Piscok Aneka Rasa" at Jl Ronggo Waluyo using variable costs, findings reveal a per-unit production cost of Rp 448.67, with 80% attributed to labor costs. Consequently, the unit price for "piscok" stands at IDR 807.61. This comparison facilitates evaluating product pricing between conventional and variable costing methods. While the business sets the selling price for the "piscok" category at Rp1.250.000, the application of variable costing results in a significantly lower price of Rp 807.61. Thus, the price discrepancy based on these methods amounts to approximately Rp 442.38. The pricing strategy adopted by Piscok Aneka Rasa in Jl Ronggo Waluyo is notably influenced by industry standards and competitors' pricing methods. Consequently, the price set by Piscok Aneka Rasa tends to surpass the corresponding rate derived from variable costing principles.